Analysis of the Effectiveness of Turmeric Flour Supplementation on Quail in the Grower Phase - Prastowo, Rizqi Adi; Mulyono, Ali Mursyid Wahyu; Sukaryani, Sri; Husein, Muhammad (Jurnal Biologi Tropis, 2025)
Turmeric (Curcuma domestica Val) contains curcumin, which enhances immunity and aids digestion in livestock. This study aimed to evaluate the effect of turmeric flour supplementation in quail rations on their growth performance. A total of 100 female grower quails (Coturnix-coturnix japonica), aged 3 weeks, were used in a completely randomized design (CRD) with four treatments and five replicates, resulting in 20 experimental units. The treatments included P0 (control, 0% turmeric flour), P1 (0.05% turmeric flour), P2 (0.1% turmeric flour), and P3 (0.15% turmeric flour). The study lasted 14 days, from 21 to 34 days of age. Observed variables included body weight gain, feed intake, and feed conversion ratio (FCR). Results indicated that turmeric flour supplementation at 0.05%–0.15% had no significant effect on quail performance. It is concluded that turmeric flour supplementation up to 0.15% does not enhance quail growth. Further studies are recommended to investigate its effects over a longer period or different growth phases.